ChemInform Abstract: Enantioselective Addition of a 2‐Alkoxycarbonyl‐1, 3‐dithiane to Imines Catalyzed by a Bis(guanidino)iminophosphorane Organosuperbase. Issue 17 (April 2016) - Kondoh, Azusa; Oishi, Masafumi; Takeda, Tadahiro; Terada, Masahiro
Abstract: The title reaction gives the adducts of type (III) with good to excellent yields and excellent enantioselectivities.